Analisa Pengaruh Pandemic Covid 19 Terhadap Konsumsi Energi Listrik di Provinsi Sulawesi Selatan Dengan Metode Regresi dan Korelasi Linear Sederhana - Hakima, Jihan (SUTET, 2024)
The level of electricity consumption in an area is affected by population growth and the COVID-19 pandemic. Forecasting electrical energy consumption is one of the important things. Using data from the past, the purpose of forecasting electrical energy consumption is to get an idea of how much electricity will be needed in the future. Therefore, it is necessary to do so in order to forecast the demand for electrical energy, especially in the province of South Sulawesi. This research was conducted to predict electrical energy sold during the 3 years of the Covid-19 pandemic and compare with calculations from PLN and BPS. This study used a simple linear regression method, and a simple linear correlation. With linear regression, it is found that the number of inhabitants has a positive influence on the amount of energy sold. With the T Test obtained RU_t= 18,326 is greater than the limit value of t_cr= 3.182, then Ho = 0 is rejected. So there is a relationship between the increase in population and the consumption of electrical energy. With a linear correlation obtained that between 0.80-1.00 is the value of the correlation coefficient, this means that the correlation is very strong that the population is very influential on the consumption of electrical energy in the province of South Sulawesi.